2023
DOI: 10.18332/tid/159137
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and reasons for quitting and transitioning between smoking and smokeless tobacco products: Findings from four waves of the ITC Bangladesh survey

Abstract: INTRODUCTION Transitions between different tobacco products are frequent among tobacco users in Bangladesh; however, the reasons leading to such transitions and why they quit are not well researched. The aim of the study is to examine perceptions and reasons reported by tobacco users in Bangladesh to transition to other products or quit. METHODS Data from four waves (2009)(2010)(2011)(2012)(2013)(2014)(2015) of the International Tobacco Control (ITC) Bangladesh Survey were used. Repeated data on perceptions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Together, the results indicate that bidis and SLT are popular in rural areas, potentially due to their lower price and the greater social acceptability for these products in rural areas, as well as among women and young people. 6 Our findings reinforce recent evidence that social and environmental factors play an important role in influencing tobacco users’ behaviours and product use transitions within the context of Bangladesh 4 and Southeast Asian countries. 41 Furthermore, our findings confirm existing evidence that suggests both person-level and contextual factors (i.e., price and affordability, etc.)…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Together, the results indicate that bidis and SLT are popular in rural areas, potentially due to their lower price and the greater social acceptability for these products in rural areas, as well as among women and young people. 6 Our findings reinforce recent evidence that social and environmental factors play an important role in influencing tobacco users’ behaviours and product use transitions within the context of Bangladesh 4 and Southeast Asian countries. 41 Furthermore, our findings confirm existing evidence that suggests both person-level and contextual factors (i.e., price and affordability, etc.)…”
Section: Discussionsupporting
confidence: 85%
“…2 In this region, tobacco is consumed in diverse forms, including smoked products, such as cigarettes and bidis (a cheaper hand-rolled form of smoked tobacco), and the widely used SLT, for which awareness of negative health effects may be limited due to culture-related customs and misbeliefs of their health effects. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…PLOS GLOBAL PUBLIC HEALTH increase could be due to various reasons. A study done in Bangladesh analysed data from 2009 to 2015 and found social factors like friends, family along with false beliefs regarding various tobacco products significantly influenced the decision to use multiple products [40]. Studies have also highlighted exposure to advertisements of tobacco products as a key role leading to consumption of a variety of tobacco products [21].…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco use accounts for an estimated 1.6 million deaths every year in Southeast Asia alone. 1 Behavioural counselling and pharmacotherapy are time-tested approaches in tobacco cessation, requiring patients to visit tobacco cessation centres (TCC). 2 However, their support is below optimum, considering fewer TCCs, shortage of dedicated staff, limited clinicians' training and skills, and the need for multiple patient reinforcement sessions.…”
Section: Introductionmentioning
confidence: 99%
“…Smokeless tobacco (SLT) use is a much more significant concern than tobacco smoking in the Southeast Asia region, which accounts for more than 80 % of global SLT users. 1 SLT cessation provided through mobile phone apps can be a promising approach in the Southeast Asian context, considering that more than 326 million people have smartphones with internet access. 15 Such apps are available on the Google PlayStore, but their quality and credibility have not been tested.…”
Section: Introductionmentioning
confidence: 99%